Japanese dichotomies and the individual identity in Haruki Murakami’s colourless Tsukuru Tazaki - Sheba D. Mani,; Ravichandran Vengadasamy,; Shahizah Ismail Hamdan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Japanese indigenous terms such as uchi/soto (inside/outside) and omote/ura (front/back) are common dichotomies employed to understand the differences between expected behaviours associated with group dynamics such as promoting collective harmony rather than individual uniqueness. Haruki Murakami advocates that the Japanese need to move away from these dichotomies in order to embrace the true self and assert an individual voice. This dictum comes after he concluded his observations on the tragic 1995 sarin gas attacks in Japan and noted that individuals should be more assertive in forming their own voice rather than conforming to the collective voice. In his latest novel, Colourless Tsukuru Tazaki and His Years of Pilgrimage (2014), he presents a new narrative on individual negotiations with group consciousness. This article seeks to reveal the sense of individuality presented through the frame of the Japanese dichotomies and the psychological response of the main character, Tsukuru. The character will be analysed in relation to the group that he belongs to: in the context of the Japanese uchi (inside) or soto (outside) and within each context, representations of his omote (front) or ura (back) is examined. The findings expose that both uchi and soto are significant in developing individuality. More importantly, how the individual responds while in these contexts determines his ability to construct his identity. This reading suggests that Murakami fulfills his agenda by empowering the individual to explore various ways in being independent. The novel also indicates that the Japanese society is gradually manifesting a growing sense of individuality by departing from its codes of group consciousness.